Abstraction, ideology and identity - Hettinga, Maria, author; Simons, Stephen, advisor; Dormer, James, advisor; Beachy-Quick, Dan, committee member; Ryan, Ajean, committee member; Tornatzky, Cyane, committee member (Colorado State University. Libraries, 2014)
My graduate work has been in printmaking, specifically monoprints. I print a variety of materials which reference landscape as well as domestic life, including common household materials such as wax paper, plastic wrap, sewing machine-stitched swatches of textiles and paper, tulle and lingerie. My personal biography is instrumental in my work; my cultural identity has played a major role in shaping my personal identity. I was raised in a Dutch immigrant farming community on the rural perimeter of Los Angeles. Domesticity, decorative arts, fashion and femininity were intertwined to create a fixed notion of beauty and to enforce a strict definition of gender roles. My insular, conservative community contrasted with the ever-changing natural environment of Southern California in the 1970s--1990s; the landscape was altered by urban expansion as well as pollution. I make abstract visual references to fashion, femininity and landscape in effort to create imagery which evades easy definition. I employ abstraction to destabilize traditional, taken-for-granted ideological narratives. While challenging authority, I promote a mindful approach to social and environmental progress which acknowledges the complexities of the twenty-first century.
Keywords: abstraction; feminine; figure; landscape; monoprint; printmaking